Analisis Tindak Tutur dalam Podcast “Close The Door” terhadap Konten Kreator Gay - Dina Olivia Sidabutar; Ester Marga Retta; Jelita Sitorus; Mutiara Aprilia; Nayla Lubis; Nurul Annisa; Regina Situmorang; Soraya Firanti; Oky Fardian Gafari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This study aims to gain a deeper understanding of the gay community, including their identity, social dynamics, and the challenges they face. In addition, this study aims to identify factors that influence public perception of the gay community and how stigma and discrimination develop. The method used is qualitative, which is a research approach that aims to understand the meaning, experience, and perspective of individuals or groups in a particular context. The data in this study were obtained from the analysis of the podcast "Close The Door" by Deddy Corbuzier which features an interview with a content creator who is part of the LGBT (gay) community. Through this analysis, the study seeks to uncover how narratives that develop in the media can influence public opinion. The results of the study are expected to provide a clearer understanding of the existence of the gay community in the social structure, as well as assist policy makers in designing regulations that are more inclusive and support diversity.